PEMBINAAN OLEH KEPALA SEKOLAH TERHADAP KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR ISLAM TERPADU UKHUWAH BANJARMASIN - Nida, Najminur Hasanatun (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2017)
Implementation of Competency Based Islamic Education Curriculum on SDIT Ukhuwah, closely related to the role of Principal as a teacher of Islamic Religious Education competence and the readiness of Islamic Religious Education teachers to improve their competence as well as competence of students. Principal Competence as a coach is supported by academic education background and teaching experience. Furthermore, the success of developing the competence of Islamic Religious Education teachers has relevance to the role of the Principal as supervisor and supervisor, as well as the discipline of Islamic Education teachers in applying their competence in the learning process. The main issue of this research is how the Principal coaching efforts on the competence of Islamic Religious Education teachers in the implementation of Competency-based Islamic Religious Education curriculum, and how the competence of teachers of Islamic Religious Education on the aspects of professional competence, personality competence, social competence, and pedagogic competence at SDIT Ukhuwah Banjarmasin. This type of research is Field Research. This research is descriptive qualitative. Principal research subjects and 4 (four) teachers of Islamic Religious Education (or PAI), while the object of research is the efforts of the Principal in fostering the competence of teachers of Islamic Education on aspects of professional competence, personality competence, social competence, and pedagogic competence. as well as the performance of teacher competence of Islamic Religious Education in learning. Technique of data collection are with observation, interview and documentary. Further data presented in the form of exposure, then in qualitative analysis which in the end drawn a conclusion by using inductive methods. The results of the field research indicate that the Principals' guidance on the competence of PAI teachers in implementing competency-based Islamic Education curriculum in the form of training has been done well, while the guidance of competence in the application of learning PAI has not been fully implemented properly, because the headmaster has not intensive conduct supervision, supervision, and assessment of PAI teachers. Similarly, PAI teachers are not competent on the application of professional competence aspects, personality competence, social competence, and pedagogic competence, because PAI teachers are less disciplined in applying Competency Based Islamic Education curriculum in learning Islamic Education on SDIT Ukhuwah Banjarmasin.